Communication plan for the nonprofit organization ACREDITAR in Coimbra - Ramalho, Filipa Daniela Oliveira (2014)
Master Project concerns the development of a Communication Plan for the Regional Nucleus of Center of Acreditar, Acreditar in Coimbra. The current economic crisis in Portugal and the fact that there is an expansion and diversification of nonprofit organizations in Portugal, push these organizations to compete increasingly with each other, in order to get the attention and contribution of individuals for their own cause, in order to be able to maintain its sustainability. So, Acreditar in Coimbra has the need to learn how can act in order to overcome this situation and stand out from the other organizations, by increasing its recognition and funds and also maintaining its sustainability. The Communication Plan suggested takes into account the specificities and limitations of such organizations, and analyzes the internal and external factors that influence and affect the Acreditar in Coimbra. To have a better knowledge and information about the organization, it was performed an interview with the coordinator of Acreditar in Coimbra, as well as the development of a focus group, to realize the relationship of individuals with these organizations and also their knowledge of Acreditar in Coimbra. The Communication Plan consists in developing a structured, effective and integrated communication strategy for Acreditar in Coimbra through partnerships and mostly through the use of online tools like interactive and direct marketing in order to reach out to its goals (to increase its recognition and its funds in order to ensure its sustainability).